TAX RESPONSIBILITY TRANSPARENCY ON E-COMMERCE TRANSACTION ACTIVITIES BYSMALL MEDIUM ENTERPRISE (SME)IN MAKASSAR CITY - Febriani Febriani; Tenriwaru Tenriwaru; Sitti Hartati Hairuddin (Magister Akuntansi, Universitas Atma Jaya Makassar, 2022)
This study aims to determine the extent of transparency of e-commerce taxaccountability by SME in the city of Makassar. This study uses a qualitative method with a descriptive qualitative approach by conducting observations and interviews and the informants used in this study are SME actors. Data collection techniques used are data reduction, triangulation, data presentation, data verification and the final conclusion of the study. The results of this study indicate that the transparency of tax accountability on e-commerce activities by SME towards income tax payments means that most SME have fulfilled their tax obligations and some of them have not fulfilled their tax obligations due to the absence of special tax rules for selling online.